Permeability evolution of shale under anisotropic true triaxial stress conditions - Li, Minghui; Yin, Guangzhi; Xu, Jiang; Cao, Jie; Song, Zhenlong (International journal of coal geology, 2016)
Although permeability data for shale have been reported previously and permeability models have been proposed, studies on permeability for shale under anisotropic true triaxial stress conditions are lacking. In this work, the permeability of shale under true triaxial stress conditions was measured using a newly developed true triaxial geophysical apparatus. The permeability always decreased with increasing principal stress. The permeability variations induced by varying each principal stress were distinct. The greatest permeability reductions were observed with increasing stress normal to the bedding planes. Based on a consideration of shale anisotropy, a permeability model was established to be applicable to shale under anisotropic true triaxial stress conditions (TTP model). This model was verified by matching the permeability data in our experiments. It was found that a more accurate match could be obtained using the TTP model, which showed advantages in reflecting the permeability changes related to increments in each principal stress. •Permeability evolution of shale under anisotropic true triaxial stress conditions•A permeability model with considerations of the effects of principal stresses•Shale permeability under true triaxial stress is matched accurately by the model.